Історія інтродукції та систематичне положення роду Hosta Tratt. - Boyko, I.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2008)
The history of introduction of Hosta Tratt. species in Europe and America is observed. The position of ge  nera Hosta Tratt. in the flowering plants systematic is analyzed.